2020
DOI: 10.1002/mrm.28484
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to measure T1‐relaxation times of macromolecules and quantification of the macromolecular resonances

Abstract: Purpose Macromolecular peaks underlying metabolite spectra influence the quantification of metabolites. Therefore, it is important to understand the extent of contribution from macromolecules (MMs) in metabolite quantification. However, to model MMs more accurately in spectral fitting, differences in T1 relaxation times among individual MM peaks must be considered. Characterization of T1‐relaxation times for all individual MM peaks using a single inversion recovery technique is difficult due to eventual contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…It has previously been reported that MM T 1 relaxation times were significantly different between GM‐ and WM‐rich voxels. M 3.75 (labeled as M 3.71 and M 3.79 in our study) and M 3.21 had the greatest difference in T 1 ‐weighting between GM and WM 38 . The same study group also reported T 2 relaxation times of MM, with smaller differences between GM and WM 39 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It has previously been reported that MM T 1 relaxation times were significantly different between GM‐ and WM‐rich voxels. M 3.75 (labeled as M 3.71 and M 3.79 in our study) and M 3.21 had the greatest difference in T 1 ‐weighting between GM and WM 38 . The same study group also reported T 2 relaxation times of MM, with smaller differences between GM and WM 39 .…”
Section: Discussionsupporting
confidence: 61%
“…M 3.75 (labeled as M 3.71 and M 3.79 in our study) and M 3.21 had the greatest difference in T 1 -weighting between GM and WM. 38 The same study group also reported T 2 relaxation times of MM, with smaller differences between GM and WM. 39 The effective T 2 varies substantially between MM signals at 3T.…”
Section: Discussionmentioning
confidence: 86%
“…It has previously been reported that MM T 1 relaxation times were significantly different between GM-and WM-rich voxels. M 3.75 (labeled as M 3.71 and M 3.79 in our study) and M 3.21 had the greatest difference in T 1 -weighting between GM and WM (Murali-Manohar et al, 2021). The same study group also reported T 2 relaxation times of MMs, with smaller differences between GM and WM (Murali-Manohar et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, when measuring macromolecules with a double-inversion preparation module a variation of ±20% requires resonance-specific variation of T 1 time constants of only tens of milliseconds (see Figure 6 in Reference 40). These variations could easily be obtained experimentally, as T 1 values have been shown to vary by hundreds of milliseconds at 9.4 T. 57 Furthermore, spurious echoes are known to particularly and erroneously influence the region where macromolecules dominate (ie 0.8 to 1.8 ppm), and although methods have been developed to address them 18,53 their manifestation is highly location and subject specific, and hence they are still commonplace as they cannot always be completely removed. As such, these artefacts would cause a similar deviation of the model from the data.…”
Section: Discussionmentioning
confidence: 99%